Application of orthogonal polynomials for analysis of input numerical data in the problems of mass transfer - P’yanylo, Ya. D.; P’yanylo, H. M.; Vasiunyk, M.Ye. (Publishing House of Lviv Polytechnic National University, 2015)
The investigations of the spectral methods are represented for solving applied tasks, in particular, the processing of digital information (problem of approximation, compression of information, filtration of signals, determination of nature of physical process which is modeled), also imposition of boundary conditions for the formulated problems of mathematical physics, etc. The essence of these methods consists in representation of known and required functions by orthogonal series in the chosen bases and construction of the algorithms for calculation of coefficients of these series (the generalized spectra). The methods of these calculation depend on the type of input information (analytic or discrete types). Approximation method for functions of two variables in domains of noncanonical form is suggested. Дослiджено спектральнi методи розв’язування прикладних задач, зокрема обробка цифрової iнформацiї (задачi апроксимацiї, стиску iнформацiї, фiльтрацiї сигналiв), визначення характеру фiзичного процесу, який моделюється, та побудови крайових умов пiд час формулювання задач математичної фiзики тощо. Суть цих методiв полягає в поданнi вiдомих i шуканих функцiй ортогональними рядами у вибраних базисах i побудовi алгоритмiв для обчислення коефiцiєнтiв цих рядiв (узагальнених спектрiв). Методи їх обчислення залежать вiд способу задання вхiдної iнформацiї (в дискретному або аналiтичному видах). Запропоновано спосiб апроксимацiї функцiй двох змiнних в областях неканонiчної форми.
Застосування ортогональних многочленiв для аналiзу вхiдних числових даних у задачах масопереносу
Keywords: orthogonal polynomials; use of spectral methods; information processing; gen- eralized spectra; ортогональнi многочлени; використання спектральних методiв; обробка iнформацiї; узагальненi спектри